A review of the experimental and numerical studies on the compression behavior of the additively produced metallic lattice structures at high and low strain rates - Muhammad Arslan Bin Riaz; Mustafa Güden (Defence Technology)
Recent advances in additive manufacturing have enabled the construction of metallic lattice structures with tailored mechanical and functional properties. One potential application of metallic lattice structures is in the impact load mitigation where an external kinetic energy is absorbed by the deformation/crushing of lattice cells. This has motivated a growing number of experimental and numerical studies, recently, on the crushing behavior of additively produced lattice structures. The present study overviews the dynamic and quasi-static crushing behavior of additively produced Ti64, 316L, and AlSiMg alloy lattice structures. The first part of the study summarizes the main features of two most commonly used additive processing techniques for lattice structures, namely selective-laser-melt (SLM) and electro-beam-melt (EBM), along with a description of commonly observed process induced defects. In the second part, the deformation and strain rate sensitivities of the selected alloy lattices are outlined together with the most widely used dynamic test methods, followed by a part on the observed microstructures of the SLM and EBM-processed Ti64, 316L and AlSiMg alloys. Finally, the experimental and numerical studies on the quasi-static and dynamic compression behavior of the additively processed Ti64, 316L, and AlSiMg alloy lattices are reviewed. The results of the experimental and numerical studies of the dynamic properties of various types of lattices, including graded, non-uniform strut size, hollow, non-uniform cell size, and bio-inspired, were tabulated together with the used dynamic testing methods. The dynamic tests have been noted to be mostly conducted in compression Split Hopkinson Pressure Bar (SHPB) or Taylor- and direct-impact tests using the SHPB set-up, in all of which relatively small-size test specimens were tested. The test specimen size effect on the compression behavior of the lattices was further emphasized. It has also been shown that the lattices of Ti64 and AlSiMg alloys are relatively brittle as compared with the lattices of 316L alloy. Finally, the challenges associated with modelling lattice structures were explained and the micro tension tests and multi-scale modeling techniques combining microstructural characteristics with macroscopic lattice dynamics were recommended to improve the accuracy of the numerical simulations of the dynamic compression deformations of metallic lattice structures.